SURVEY PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS SMAN 1 GEDANGAN SIDOARJO - GANIS ANISA NINGRUM (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
The purpose of study is to know the using of teaching material in SMAN 1 Gedangan and the decent of teaching material. The function of study can be used as reference material of using a teaching material in accounting class. The approach of study is descriptive study with quantity approach. The subject of study is accounting teacher of elevent social class, and the object of study is teaching material applied in the learning teaching process in eleventh social class. The results of this study are Festive materials used in SMAN 1 Gedangan a Module